Strength reduction factor evaluation of the circular reinforced concrete column with varying eccentricity ratio (e/h) - Wahyuniarsih Sutrisno; Mudji Irmawan; Dwi Prasetya (Journal of Civil Engineering, 2020)
This paper presents strength reduction factor evaluation of circular reinforced concrete column with varying eccentricity ratio (e/h) using the first-order-reliability-methods. The resistance properties of the reinforced concrete column is estimated using the monte-carlo simulation with random normally distributed material properties. Only dead and live load combination considered in the analysis. The parameters being investigated when evaluating the resistance of the reinforced concrete column are the concrete compressive strength, steel yield strength, coefficient of variation for both the concrete and steel materials, reinforced concrete column size, and the longitudinal reinforcement ratio. When evaluating the strength-reduction factor, the safety index values are 3.0, 3.5, and 4.0. From the analysis, it was found out that the strength reduction factor, for e/h higher than one and with safety index equal to 3.0, was equal to 0.9 which agrees well with the ACI 318 strength reduction factor for tension-controlled region. However, for e/h lower than one and safety index equal to 3.0, the strength reduction factor was equal to 0.6 which was lower than the ACI 318 strength reduction factor for compression-compression controlled region.